Differentiated Standards and Patent Pools1. (June 2014) - Schiff, Aaron; Aoki, Reiko
Abstract We consider patent pool formation by owners of essential patents for differentiated standards that may be complements or substitutes in use. Pooling improves coordination in terms of royalty setting within a standard but provokes a strategic response from licensors in the competing standard. We characterise the incentives to form and defect from pools within standards and show how pool formation and stability depend on competition between standards. We also examine strategic patent pool formation by consortium standards and show that policies promoting compatibility of standards may increase or decrease welfare depending on the effects on the incentives to form pools.